Mixed families and parenting strategies : the case of mixed couples living in Italy formed by Italian and African parents - (:unkn) unknown (My University, 2018)
This research studies socialization and education of children born from mixed-couples formed by an Italian and an African sub-Saharan parent, living in Italy. The study is developed within an ecological framework of families, and it is based on theoretical knowledge gained from studies concerning mixedness and acculturation processes. Our aim is to better understand identity, culture and education strategies developed by parents, and the way parents perceive such strategies. Three complementary directions of research are explored: migratory experience and union formation, transmission of identity and culture, and parenting strategies. The empirical stage of the research is based on a qualitative methodology. The investigation concerned 19 families; 18 mothers and 11 fathers were interviewed by narrative techniques. The results show the interaction between the African parent migratory experience and family dynamics. The various dimensions of the mixed familiar contexts (linguistic, religious, ethnic, cultural, social) create unique family profiles. Several factors impact parenting strategies: migration, socioeconomic background, stigmatization, « migration of contact and internal migration », relationships with the extended family and transnationalism, and social relationships. Social context is decisive. The perception of racial discrimination hinders dealing with differences. Supportive social networks, valorization of migrant culture, and sharing common values help parents to overcome these difficulties. This research provides a new knowledge about an emerging familiar context.
Keywords: African Research